Virus-modified paraspeckle-like condensates are hubs for viral RNA processing and their formation drives genomic instability - Katherine L. Harper; Elena M. Harrington; Connor Hayward; Chinedu A. Anene; Wiyada Wongwiwat; Robert E. White; Adrian Whitehouse (Nature Communications)
Abstract The nucleus is a highly organised yet dynamic environment containing distinct membraneless nuclear bodies. This spatial separation enables a subset of components to be concentrated within biomolecular condensates, allowing efficient and discrete processes to occur which regulate cellular function. One such nuclear body, paraspeckles, are comprised of multiple paraspeckle proteins (PSPs) built around the architectural RNA, NEAT1_2. Paraspeckle function is yet to be fully elucidated but has been implicated in a variety of developmental and disease scenarios. We demonstrate that Kaposi’s sarcoma-associated herpesvirus (KSHV) drives formation of structurally distinct paraspeckles with a dramatically increased size and altered protein composition that are required for productive lytic replication. We highlight these virus-modified paraspeckles form adjacent to virus replication centres, potentially functioning as RNA processing hubs for viral transcripts during infection. Notably, we reveal that PSP sequestration into virus-modified paraspeckles result in increased genome instability during both KSHV and Epstein Barr virus (EBV) infection, implicating their formation in virus-mediated tumourigenesis.